2010
DOI: 10.1016/j.bbabio.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Photoconsumption of molecular oxygen on both donor and acceptor sides of photosystem II in Mn-depleted subchloroplast membrane fragments

Abstract: Oxygen consumption in Mn-depleted photosystem II (PSII) preparations under continuous and pulsed illumination is investigated. It is shown that removal of manganese from the water-oxidizing complex (WOC) by high pH treatment leads to a 6-fold increase in the rate of O(2) photoconsumption. The use of exogenous electron acceptors and donors to PSII shows that in Mn-depleted PSII preparations along with the well-known effect of O(2) photoreduction on the acceptor side of PSII, there is light-induced O(2) consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 31 publications
7
31
0
Order By: Relevance
“…and Ca 2? at catalytic concentrations (Yanykin et al 2010(Yanykin et al , 2013Khorobrykh et al 2011). In this study, we experimentally verified the suggestion that molecular oxygen (rather than superoxide anion radical formed on the acceptor side of PSII) is directly involved in the donor-side photoinhibition of Mn-depleted PSII membranes.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…and Ca 2? at catalytic concentrations (Yanykin et al 2010(Yanykin et al , 2013Khorobrykh et al 2011). In this study, we experimentally verified the suggestion that molecular oxygen (rather than superoxide anion radical formed on the acceptor side of PSII) is directly involved in the donor-side photoinhibition of Mn-depleted PSII membranes.…”
Section: Introductionsupporting
confidence: 79%
“…In the PSII membranes holding intact WOC, the O 2 photoconsumption rate was very low (2 lmol (mg of Chl) -1 h -1 ), but after removal of Mn from the WOC, the rate was 6-fold higher Yanykin et al 2010). The study of this process showed that in Mn-depleted PSII membrane fragments, the O 2 photoconsumption is associated (about 70 %) with the generation of the long-lived states of P 680…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations